Man Made Law Vs. Law of Nature in Sophocles Plays (Voice: A Biannual & Bilingual Journal, 2025)
Justice is forced by the state or authority in equal measures to all. This research points out the problems in ancient Greek beliefs on rationality, justice, and morality while reading Sophocles' plays from the Oedipus trilogy, Oedipus the King and Antigone. Those notions appear utilitarian, forced by the state or authority to all the people without discrimination. The entire state suffers from barrenness and famine, a punishment in Greek myths. In the cases of Oedipus and Creon, the state suffers from plague and famine due to its own fault, and all innocent Greek citizens bear its consequences without discrimination. How does this make sense as justice? Why is the individual not rewarded or punished based on the amount of good or criminal work s/he has committed? It is giving everybody the same reward or punishment without discrimination. Is it morally or rationally, correct? The Greek notions of justice and morality present several problems when considered. The issue will be analysed from the recent perspective of justice and the utilitarian thought proposed by various thinkers.